Smart leadership : four simple choices to scale your impact - Miller, Mark, 1959- (Ascent Audio, 2022)
Escape the mediocrity that ensnares so many in business and become a better, more effective leader. Have you ever wondered what it would take to be a better leader, or achieve your wildest dreams, or make a bigger difference in the world? The answer lies in the choices you make: about everything from how you spend your time to the way you view the world. Smart Leadership is the latest essential business title from internationally bestselling author of Win the Heart and Chess Not Checkers, Mark Miller. In this book, he shares the four research-based "smart choices" the best leaders make to scale their influence and results. By teaching you how to confront reality, grow capacity, fuel curiosity, and create change, Miller will help you: bring fresh eyes and fresh thinking to your leadership approach; increase your confidence in your ability to make a difference; lead at levels you never thought possible; and accelerate your learning curve so that all these benefits come faster and more naturally. With this guide, your leadership-and your life-will be transformed forever.